SPREADING OF A NAPL LENS IN A DOUBLE-POROSITY MEDIUM - Ryzhik V. (My University, 2007)
Spreading of a non-aqueous phase liquid (NAPL) denser than water (DNAPL) lens (mound) in the unsaturated zone of double-porosity aquifer above an impervious plane boundary is investigated. The double-porosity aquifer is conceptualized as a fracture network surrounding pervious blocks. Vertical gravity equilibrium is assumed to prevail in each one of the two media, fractures and blocks. Through vertical integration, two coupled partial differential equations for the DNAPL content in each medium are obtained. The mass exchange rate between high- and low-permeability media is considered as a function of NAPL content. The dominant effect is gravity, whereas capillary forces are negligible. Analytical solutions for one-dimensional and axisymmetric problems of mound spreading are obtained.
Keywords: AQUIFER CONTAMINATION; DOUBLE-POROSITY MEDIUM; NAPL MOUND SPREADING; UNSATURATED ZONE